2006
DOI: 10.1080/00207450600553141
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation in Patients With Brain Tumor

Abstract: Molecular and genetic signatures may predict brain tumor behavior and may soon guide tumor classification, diagnosis, and tumor-specific treatment strategies. Free oxygen radicals (FOR) are thought to take part in oncogenesis and cellular differentiation. This article explored the state of FORs and antioxidant system in patients with cerebral tumor. The serum concentrations of malondialdehyde (MDA), catalase, and glutathione peroxidase (GSH-Px) enzyme activities were measured in the serum of 35 patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…In contrast, increases of GPx and GRx concentrations were shown in some brain tumors and brain metastasis. In a most recent study, Yilmaz et al (2006) studied the serum concentrations of malondialdehyde (MDA), a by-product of lipid peroxidation, CT and GPx in 35 patients with gliomas or meningiomas and in 11 healthy controls. They found that mean serum levels of MDA, CT and GPx were signiWcantly higher for both gliomas and meningiomas when compared to the controls and no diVerences were found between gliomas and meningiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, increases of GPx and GRx concentrations were shown in some brain tumors and brain metastasis. In a most recent study, Yilmaz et al (2006) studied the serum concentrations of malondialdehyde (MDA), a by-product of lipid peroxidation, CT and GPx in 35 patients with gliomas or meningiomas and in 11 healthy controls. They found that mean serum levels of MDA, CT and GPx were signiWcantly higher for both gliomas and meningiomas when compared to the controls and no diVerences were found between gliomas and meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Altered activity of GPx has also been demonstrated in various types of cancers (Punnonen et al 1994;Wasowicz et al 1994). However; little information is available in the literature in relation to brain cancers (Rao et al 2000;Pu et al 1996;Dudek et al 2002a, b;Yilmaz et al 2006). Furthermore, much has been written about the SODs and CTs in malignant cells and tumors during the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , BA was able to decrease in significant manner the production of MDA and 4‐HNA (the main products derived from lipid peroxidation) from glioblastoma cells under proinflammatory conditions. Lipid peroxidation is a key mechanism involved in glioblastoma cell growth and survival (Yilmaz et al, ). Lipid peroxidation responsiveness to LPS was similar for both glioblastoma cells (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation is a key protumorigenic factor in several tumors (Yilmaz et al, 2006); in fact, MDA is a lipid peroxidation product with well-known mutagenic properties (Niedernhofer, Daniels, Rouzer, Greene, & Marnett, 2003). Cancer patients with increased plasma levels of MDA or 4-HNA have a negative prognosis of the diseases (Gönenç, Ozkan, Torun, & Simşek, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports show an inverse association of antioxidants or carotene alone intake with glioma (2)(3)(4), whereas others do not (5,6). Some studies have shown a correlation between the presence of GBM and oxidative stress (7), or lipid peroxidation (8). The brain is one of the tissues the most sensitive to oxidative stress because of the high contents of oxidizable substrates and the low antioxidant levels.…”
Section: Introductionmentioning
confidence: 96%